Estudo de megacariócitos e da expressão de NS3 em pulmões de casos de dengue fatal: associação clínico-patológica - Lopes, Renata Lima (2023)
Dengue is a viral Dengue is a viral disease that has been worryingly expanding worldwide for decades. In Brazil, dengue is endemic with epidemic peaks. There are some gaps in the understanding of dengue pathogenesis, especially in severe cases leading to death, it continues to be a significant health threat in the affected regions. In vivo studies of human dengue fatal cases can significantly contribute to identifying involved cells in DENV replication, which contributes to thrombocytopenia associated with the severity of dengue. The objective was to identify and quantify lung megakaryocytes, evaluate the correlation between clinical and anatomopathological data with platelets, and identify the presence of NS3 in lung megakaryocytes in cases of severe and fatal dengue fever. A retrospective postmortem observational study was carried out using paraffin blocks of lung tissue from 34 dengue fatal cases occurred in Ceará.All underwent autopsy at the Death Verification Service (SVO) between 2011 and 2013, and all had clinical and laboratory diagnosis of dengue and were duly notified to the Epidemiological Surveillance Center of theCeará Department of Health. The lung tissues were prepared for identification of megakaryocytes by HE stain, immunohistochemistry with anti-CD61 monoclonal antibodies to confirm the identification and quantification of lung megakaryocytes, and demonstration of the indirect presence of viral replication in megakaryocytes with anti-NS3. Lung parenchymal images were captured at 400x magnification, marked with anti-CD61 and anti-NS3 antibodies. A higher average of lung megakaryocytes was found in dengue patients than the control group, presenting a statistically significant difference (5.32 ± 2.69 vs. 2.61 ± 1.97 respectively, p < 0.001). The majority of patients showed bleedingwarning signs (55.88%) and hemorrhage signs at autopsies (91.18%). Regarding thrombotic events, they occurred in 35.29% of fatal dengue cases and 58.33% of thrombotic events were pulmonary. The results also revealed that 38.24% of dengue patients had pulmonary megakaryocytes stained against NS3, confirming the presence of DENV replication in these cells. In summary, it was demonstrated an increase in the number of lung megakaryocytes and the in vivo NS3 expression in lung megakaryocytes from patients with severedengue fever, indicating that DENV can infect these cells, compromising platelet production, therefore contributing to an unfavorable prognosis.